Beitrag zur Kenntnis der ostpaläarktischen Yponomeutidae (Lepidoptera). - Friese, Gerrit (Contributions to Entomology = Beiträge zur Entomologie, 1962)
In addition to the recently published reviosional work on the palearctic Yponomeutidae the hitherto described species from Japan and China are summarized and studied as far as authentic material was available. Of the 44 species hitherto known from the east-palearctic region 16 species of Pseudocalantica Friese, Yponomeuta Latr., Nordmaniana Friese, Zelleria Stt., Metanomeuta Meyr. and Ocnerostoma Zell. are discussed in detail. Metanomeuta zonoreros Meyr. was found synonym to Metanomeuta fulvicrinis Meyr., and Paradoxus lushanensis Gozm. to Nordmaniana trachydelta (Meyr.); Hyponomeuta usuguronis Mats. being the same as Homadaula anisocentra Meyr., a species, which is to be placed in the genus Paraprays Rbl. (Plutellidae). Ypomeuta vigintipunctatus (Retz.), Zelleria hepariella Stt., and Ocnerostoma piniariellum Zell. are recorded as new to Japan. Male and female genitalia of 11 species are figured and described for the first time.Nomenclatural Actsusugorinis Matsumura, 1931 (Hyponomeuta), syn. n. of Homadaula anisocentra Meyrick, 1922fulvicrinis Meyrick, 1935 (Metanomeuta), Lectotypezonoceros Meyrick, 1935 (Metanomeuta), Lectotype; syn. n. of Metanomeuta fulvicrinis Meyrick, 1935lushanensis Gozmány, 1960 (Paradoxus), syn. n. of Nordmaniana trachydelta (Meyrick, 1931)cinefactus Meyrick, 1935 (Yponomeuta), Lectotype